Recurrent rectal cancer causing lumbosacral plexopathy with perineural spread to the spinal nerves and the sciatic nerve: An anatomic explanation. Issue 1 (5th August 2014) - Capek, Stepan; Sullivan, Patrick S.; Howe, Benjamin M.; Smyrk, Thomas C.; Amrami, Kimberly K.; Spinner, Robert J.; Dozois, Eric J.
<x xml:space="preserve">Abstract</x> Several groups have reported cases of rectal cancer with carcinomatous involvement of the lumbosacral plexus and sciatic, obturator, pudendal, or spinal nerves. To our best knowledge, clear examples of perineural tumor spread in rectal carcinoma have not yet been described. We retrospectively reviewed clinical data and imaging studies of three patients with primary or recurrent rectal cancer involving the lumbosacral plexus. Imaging studies included MRI and 18FDG PET/CT scans in all (n = 3) patients, histological samples were available in two (n = 2). Imaging studies demonstrated distinct features of tumor spread from the organ to the plexus and beyond in all cases (n = 3), histological specimens demonstrated perineural involvement thus supporting our theory (n = 2). We present these three cases of perineural tumor spread in rectal cancer as a proof of concept. We hypothesize that not only our cases, but other similar reported cases can be explained anatomically by extension of the rectal cancer to the inferior hypogastric plexus with perineural tumor spread to the lumbosacral plexus using the pelvic and sacral splanchnic nerves as conduits. Once the tumor reaches the lumbosacral plexus, it can continue to spread proximally or distally. We believe that perineural spread of colon cancer represents an important, under‐recognized mechanism of recurrence to neighboring major nerves in the pelvis. Clin. Anat. 28:136–143, 2015. © 2014 Wiley Periodicals, Inc.